Playing with history : the historical approach to musical performance - Butt, John (Musical performance and reception., 2002)
Why do we feel the need to perform music in a historically informed style? Is this need related to wider cultural concerns? In the most ambitious study of the topic to date, John Butt sums up recent debates on the nature of the early music movement and historically informed performance, calling upon a seemingly inexhaustible fund of ideas gleaned from historical musicology, analytic philosophy, literary theory, historiography and theories of modernism and postmodernism. He develops the critical views of both supporters and detractors of the movement, while claiming ultimately that it has more intellectual and artistic potential than its detractors may have assumed. He also asks whether the phenomenon of historically informed performance reflects changes in the culture of western music and how it, in turn, may have influenced that culture, particularly in regard to such issues as the status of the composer, the work, intentionality and notation.--Publisher description.